Liver damage during infections with coronavirus - Iqbal Hanash Dhefer (Journal of Techniques)
The pathogen of the new 2019 coronavirus disease (COVID-19), the sever acute respiratory syndrome coronavirus 2 (SARS-Cov-2), presented a significant risk to health care. The WHO has described the SARS-CoV-2 infection outbreak as an international public health emergency. The main damage caused by the infection with SARS-CoV-2 was known to be lung infections. Previous research revealed that liver damage is prevalent in patients infected with the additional widely zoonotic coronaviruses, Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS), and has been reviewed in relation to the severity of MERS, SARS, and COVID-19 diseases. Likewise, the mechanism and features of liver damage and liver injury has also been observed, as outlined in this review, which results in extreme cases during the phases of the disease.